Pendampingan Pemanfaatan Limbah Konveksi Rumah Tangga (Pelakort) Dengan Teknik Blended Di Desa Embung Kandong Kecamatan Terara - Susanti, Dwi Rahayu; Agus Muliadi Putra; Wajizatul Amnia (Universitas Hamzanwadi, 2024)
Convection waste consists of leftover fabric from daily clothing production by some members of the community. The convection produced includes various types of fabric that result in garments such as school uniforms, pillowcases, prayer garments, nightgowns, dresses, and more. Before becoming clothes, the fabric is cut according to the model. after the fabric is cut into parts of the garment, this process produces fabric scraps or what is called patchwork fabric. Because patchwork fabric is the result of small cuts, the technique used in making products such as mats or pouches is the Blended Technique to make it more effective in its utilization. At first glance, these leftover fabric pieces seem useless, but in reality, the remnants from cutting clothes can be utilized to create something useful or products that are more beneficial than being discarded as waste. It is better to use them as more useful items. Convection waste, if not properly managed, can have a negative impact on our surrounding environment. This is because textile waste has characteristics such as a slow decomposition rate, the potential to damage soil biota, the ability to pollute the air when burned, and the capacity to clog waterways, leading to flooding. Therefore, we provide assistance in processing patchwork fabric waste, which is reprocessed into products with higher economic value by turning the fabric waste into more useful items, such as mats, flower pots, hair ties, mask connectors, and so on, using the Blended Technique sewn with a sewing machine. In addition to being environmentally friendly, it has economic value when sold and can increase income for the community